Single-Step Synthesis of Platinoid-Decorated Phosphorene: Perspectives for Catalysis, Gas Sensing, and Energy Storage - Kovalska, Evgeniya; Luxa, Jan; Melle-Franco, Manuel; Wu, Bing; Marek, Ivo; Roy, Pradip Kumar; Marvan, Petr; Sofer, Zdenek (ACS applied materials & interfaces, 2020)
The originality of phosphorene is suppressed by its structural defects, irreproducibility, and sensitivity to the ambient environment. To preserve phosphorene's essential characteristics, for example, influencing the charge redistribution and generating the formation of active centers, noble-metal decoration is found to be an efficient approach. Herein, we demonstrate a single-step electrochemical synthesis of platinoid-decorated few-layer phosphorene (FP). The material's structure and effects of metal (Ru, Rh, and Pd) deposition on the FP nanosheets were first explored by numerous analytical techniques and theoretical calculations. Platinoid-decorated FPs demonstrate high quality and consist of one to five layers modified with round- and heptagon-shaped metal nanoparticles with the most intense distribution of Pd. The high-rate Rh deposition provides the enhanced electrocatalytic efficiency for hydrogen evolution (79 mV·dec-1-Tafel slope) and almost 20 times increased capacity for the Li-ion batteries in comparison to bare and Ru-decorated FP. The chemosensing of platinoid-decorated FP indicates a response to methanol plus ethanol and shows inertness to acetone. The incorporation of Ru and Rh nanoparticles increases FP's selectivity toward methanol. This research provides a new approach for the in situ FP functionalization during top-down synthesis and thus broadens the material's feasibility for advanced nanotechnology.
Keywords: gas sensing; electrochemical exfoliation; energy storage; platinoid-decorated phosphorene; energy conversion